Learning Trajectory for Teaching the Mean Concept Using Problem-Based Learning and Animated Video - Aripin, Usman; Rosmiati, Tanti; Rohaeti, Euis Eti; Hidayat, Wahyu (Mathematics Education Journal, 2025)
Conceptual understanding is a critical component of effective mathematics learning. However, many students encounter challenges in understanding mathematical concepts, including the concept of the mean. This study aims to design a learning trajectory that enhances students’ conceptual understanding of the mean. Employing a design research methodology, the study followed the stages of validation studies in creating and refining a hypothetical learning trajectory (HLT). The research consisted of three stages: preliminary design, design experiment (encompassing pilot experiment and teaching experiment), and retrospective analysis. The participants were fourty eighth-grade students from a public school in Cimahi. Data were collected through interviews, observations, documentation, and field notes, which informed iterative improvement to the HLT. Data analysis involved comparing students’ actual learning experiences with the HLT as a reference framework. The findings reveal that integrating technology and problem-based learning enhances students’ conceptual understanding of the mean, fostering creativity and real-world problem-solving skills. Based on these results, this study proposes a validated learning trajectory to support students in developing a deeper conceptual understanding of the mean.